The Production of Liquid Soap Using Locally Sourced Groundnut Oil and Optimization of its Physicochemical Properties - Salisu, Umar Muhammad; Ahmad, Mubarak Ibrahim; Ibrahim, Yusuf; Ahmed, Fahad; Ibrahim, Haruna Sanusi (Journal of Material Science and Radiation, 2026)
Creating liquid soap with locally sourced oils is not just a smart choice for your wallet, but it’s also a sustainable option compared to imported soaps. This study zeroed in on making liquid soap from groundnut oil and fine-tuning its physicochemical properties like pH, viscosity, foam ability, total solids, and stability. We prepared four different formulations by tweaking the amounts of potassium hydroxide (KOH), glycerol, and sodium chloride (NaCl). The soap samples were put through standard lab tests. The results showed that all formulations had pH levels within the acceptable range (9–10), and we noticed that viscosity, foam height, and total solids increased with higher concentrations of glycerol and NaCl. Stability tests conducted over four weeks revealed that Samples B, C, and D held up well with no phase separation, while Sample C (100 g oil, 11 g KOH, 4% glycerol, 1.5% NaCl) struck the perfect balance of physicochemical properties, aligning with international liquid soap standards. The study wrapped up by confirming that groundnut oil is a great choice for producing high-quality liquid soap, providing an affordable and locally available raw material for both small-scale and industrial production. We recommend diving deeper into optimization studies, conducting microbial analyses for shelf-life evaluations, and encouraging the use of groundnut oil-based liquid soap in local industries to boost sustainability and economic growth